THE SOLIDARITY OF THE MECHANICS OF THE CHINESE AND JAVANESE COMMUNITIES IN MAINTAINING RELIGIOUS HARMONY IN PAKELAN VILLAGE KEDIRI CITY - Raden Karebet Uki (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
The Kediri area is divided into two, the City area and the Regency area. The city area contains 3 sub-districts. Pakelan sub-district is located in the Kota District area, precisely west of Jl. Doho, Kediri city. The Pakelan area is known as an ethnic Chinese area, because the majority of the population in this area is Chinese and Javanese. The existence of two different ethnicities will automatically influence socio-cultural conditions in social interaction and social solidarity. This research uses a social-anthropological approach with qualitative descriptive explanation. In general, there are two conditions for creating social interaction, namely, first, social contact and communication. Based on field results, social solidarity and social interaction for the first time between Chinese and the Javanese especially in Kediri, occurred in the form of labor. Chinese people employ local people to help with their work, transporting and unloading ethnic Chinese merchandise that has just arrived from Sungai Brantas Port. From this pattern of organic solidarity it then spreads to mechanical solidarity. When social interaction between them increases, it indirectly fosters harmony and harmony between religious communities